Effect of Curcuma longa Supplement on Cognitive Performance in Swiss Albino Mice (Gadau Journal of Pure and Allied Sciences, 2024)
Dementia is an age-related mental disorder and a characteristic symptom of various neurodegenerative disorders. Hyperglycemia affects areas of the brain crucial for learning and memory processes, potentially leading to cognitive impairments in individuals with diabetes. Curcuma longa (C. longa) contains many pharmacological and chemically important compounds with many beneficial effects. This study aimed to evaluate the effect of Curcuma longa on cognitive function in Swiss albino mice. A total of sixteen (16) mice of both sexes weighing between 24 – 30 grams were used for the study. The mice were divided into four groups of four mice each (N=4). Group I served as control and received 10 ml/kg distilled water; groups II, III and IV were given 5%, 10% and 20 % of Curcuma longa for 14 days respectively. Y maze and novel object recognition task were used to assess spatial working, long-term and recognition memories respectively. We observed that the 5% C. longa (77.60 ± 10.15%) group showed significant (p < 0.05) improvement in percentage alternation compared to the control group (64.40 ± 5.99%). We also found out that the 5% C. longa supplemented group showed a significant (p < 0.05) increase in both long-term memory (-14.08 ± 3.26) and discriminative index (-0.26 ± 0.07) when compared to control group (-31.55 ± 2.65) and (-0.33 ± 0.07) respectively. Thus, C. longa supplement at 5% improves spatial working memory, long-term memory and discriminative index of Swiss albino mice.
Keywords: Curcuma longa; dementia; spatial working memory; long-term memory